Inverse Kinematics and Reachable Workspace of UPS/UPR/SP Parallel Mechanism - Longfei Li; Yaohong Zhao; Bin Sun; Ruiqin Li; Guowang Pang (Jixie chuandong)
Considering that the sorting of goods is time-consuming，laborious and not accurate enough，a UPS/UPR/SP parallel mechanism is proposed，which is considered to be applied in the field of packaging sorting to liberate both hands. Firstly，the degree of freedom of UPS/UPR/SP parallel mechanism is analyzed by using screw theory，and the degree of freedom of the mechanism is analyzed and verified based on the improved Kutzbach-Grübler formula； then，particle swarm optimization （PSO） algorithm and closed vector method are used to solve the forward and inverse solutions of the mechanism，and the reachable workspace of the mechanism is solved by using the limit search method in Matlab software； Finally，the mechanism is applied to the express sorting with high accuracy of position accumulation. The results show that the UPS/UPR/SP parallel mechanism has three degrees of freedom of two rotations and one movement，the end movement of the moving platform is accurate，and the workspace is continuous and uninterrupted. The mechanism is flexible and can fully meet the requirements of express logistics.